Ion-exchange removes hexavalent chromium from drinking water. Issue 10 (October 2015) - Unknown
Abstract : In the USA, Envirogen Technologies Inc has started up a high-efficiency ion-exchange system for the treatment of hexavalent chromium in drinking water supplies for California Water Service (Cal Water) in Salinas.